Clinical manifestations and outcomes of tuberculosis in children in the Irkutsk region - S. G. Zvonkova; E. Y. Zorkaltseva; S. V. Pugacheva (Acta Biomedica Scientifica)
100 children were observed. Tuberculosis of inrathoracic lymph nodes was found in 79 (79,0 %) patients, complicated tuberculosis - in 29 (36,7 %) of 79 patients. The phase of reverse development of tuberculosis was detected in 47,0 % of children with TB. Due to the slow dynamics of the disease, the duration of chemotherapy in 75,0 % of children was 240 days. In the mode of treatment, drug resistance of a patient in lesion of tuberculosis infection is taken into account. As a result of treatment, resorption of infiltration in the lungs was observed in 15,0 %, fibrosis - in 26,0 %, formation of small calcifications - in 39,0 %, formation of multiple large calcifications - in 20,0 % of children. The cause of the formation of calcifications is the late detection of tuberculosis. In children with the formation of calcifications throughout the course of treatment the number of leukocytes decreased, the downward trend in the absolute number of lymphocytes to the 4th month of treatment was traced, the content of leukocytes increased to the end of primary treatment. In children without formation of calcifications the reduction of leukocytes and lymphocytes was not identified during the treatment. The decrease in the content of leukocytes and lymphocytes may explain long-term persistence of endogenous intoxication.